Phantom hCG and Phantom Choriocarcinoma - Laurence A. Cole (1998)
Phantom hCG and phantom choriocarcinoma syndrome (pseudohypergonadotropinemia) refers to persistent mild elevations of hCG, leading physicians to treat patients with cytotoxic chemotherapy for choriocarcinoma when in reality no true hCG or trophoblast disease is present. We report here three cases of the phantom hCG and phantom choriocarcinoma syndrome referred to the hCG Reference Service. In the first case, low levels of hCG were detected in serum (49 to 89 IU/liter) 11 months after the patient had a miscarriage. The presumptive diagnosis of choriocarcinoma was made. After two courses of chemotherapy and a hysterectomy low levels of hCG were still detected. Samples were sent to the hCG Reference Service. While low levels of hCG were detected in serum by three different assays (17, 22, and 9.2 IU/ml), no hCG was detected in the urine. When serum was diluted, levels did not decrease parallel to the dilution. The lack of dilutional parallelism and absence of urine reactivity indicated that the molecule measured was a pseudogonadotropin or phantom hCG, an interfering substance in hCG tests. Therapy was halted. In the second case, a positive serum pregnancy test was recorded 7 years after a normal pregnancy. A pelvic ultrasound and a laparoscopy revealed no pregnancy. Blood hCG levels stayed between 48 and 74 IU/liter over a 3-month period. Samples were sent to the hCG Reference Service. Low levels of hCG, free β-subunit, and β-core fragment were detected in serum using four specific assays. No hCG immunoreactivity was found in the urine sample. None of the four assay results declined parallel to dilution. Again, phantom hCG was diagnosed. In the third case, a positive serum pregnancy test was recorded 1 year after the patient had a normal pregnancy. A pelvic ultrasound revealed no fetal sac. Low levels of hCG (51–135 IU/liter) persisted for 3 months. A preumptive diagnosis of choriocarcinoma was again made. After three cycles of chemotherapy, low levels of hCG were still detected. Samples were sent to the hCG Reference Service. Low levels of hCG immunoreactivity were detected in serum in just one of three hCG assays (13 IU/liter). No immunoreactivity was detected in the urine sample. Again, phantom hCG was diagnosed, and all therapy was halted. Care is needed in interpreting persistent low levels of hCG in patients with no history of trophoblast disease. It is important for the laboratory to show dilutional parallelism in the hCG results and presence of hCG in serum and urine samples in order to exclude phantom hCG before diagnosing choriocarcinoma.